2020
DOI: 10.1093/geront/gnaa125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Modified Mindfulness-Based Cognitive Therapy for Family Caregivers of People With Dementia: A Randomized Clinical Trial

Abstract: Background and Objectives Family caregivers of people with dementia (PWD) experience high levels of stress resulting from caregiving. This study aimed to investigate the effects of a modified of Mindfulness-Based Cognitive Therapy (MBCT) for dementia caregiving Research Design and Methods 113 family caregivers of PWD were randomized to either the intervention group, receiving the 7-session modified MBCT over 10 weeks with tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(88 citation statements)
references
References 41 publications
2
84
0
2
Order By: Relevance
“…The study designs of all studies are presented in Table 1 . The seven studies included were those by Cheung et al, (2020) [ 39 ]; Kor et al, (2019, 2020) [ 40 , 41 ]; Norouzi et al, (2015) [ 42 ]; Oken et al, (2010) [ 36 ]; Ozen (2013) [ 43 ]; and Zarei (2018) [ 44 ]. All included studies were randomized and controlled.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study designs of all studies are presented in Table 1 . The seven studies included were those by Cheung et al, (2020) [ 39 ]; Kor et al, (2019, 2020) [ 40 , 41 ]; Norouzi et al, (2015) [ 42 ]; Oken et al, (2010) [ 36 ]; Ozen (2013) [ 43 ]; and Zarei (2018) [ 44 ]. All included studies were randomized and controlled.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were described as pilot RCTs [ 35 , 40 , 43 ]. The number of participants in the seven studies ranged from 12–113, with only two studies [ 39 , 41 ] recruiting over 50 participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meguro [5] suggested that expression and attitude of a patient with AD differed during an examination depending on whether the family of the patient had suggested that he or she was forgetful. Kor et al [19] found that an increase in the mindful attitude of caregivers was significantly correlated with a decrease of behavioral and psychological symptoms of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…(7) A group-based multicomponent psychoeducation intervention was grounded in the Adult learning theory, Stress, appraisal and coping theory and Cognitive behavior therapy, which aims to reduce caregiver depression, and improve caregiving appraisals and coping skills, and improve the conditions of people with dementia [64]. In addition, the mechanism of a modified mindfulness-based cognitive therapy is the mindful coping model [67].…”
Section: Theory Basis and Caregiver Needs Assessment For Interventionsmentioning
confidence: 99%